An overview of the engine remanufacturing process based on independent remanufacturers in Malaysia - Muhammad Syafiq Sulaiman,; Dzuraidah Abd Wahab,; Siti Maisarah Mohd Pisal,; Mohd Radzi Abu Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The automotive remanufacturing industry is the largest remanufacturing sector, accounting for around two-thirds of global remanufacturing activities. Engine parts are a common target for remanufacturing due to their high value and demand. With the introduction of the National Automotive Policy (NAP) 2020 in Malaysia, many small and medium-sized enterprises (SME) are progressively taking part in the remanufacturing industry, especially engine remanufacturing. However, since the remanufacturing process is more complex than the primary production of the same products, challenges partaking in the operations and processes of remanufacturing are common in the industries, especially for independent remanufacturers. There still lacks data that shows the process flows of these engine-remanufactured products being conducted locally. In this study, a qualitative interview has been conducted through focus group discussion (FGD) with the SMEs to determine the processes and practices for automotive remanufacturing, thereby identifying key components of engine remanufacturing. Four different category questions, accompanied by several sub-questions to determine the processes and methods in their aspects of automotive remanufacturing, have been asked. The findings show that engine remanufacturing is a series of intricate processes being done carefully and extensively, from the cleaning process to the final assembly testing for which varies heavily depending on the components and industries. While the remanufacturing processes across the independent remanufacturers are almost the same, findings also suggest there exist additional processes that can be applied to increase the lifespan of the products, such as additive remanufacturing techniques, that these independent remanufacturers know but do not apply to their processes due to the cost and economics of the business. Further research exploring case studies of these independent remanufacturers is recommended to ensure a more holistic and critical aspects of engine remanufacturing to be captured.